Densification mechanisms and microstructural evolution during spark plasma sintering of boron carbide powders. Issue 4 (March 2018) - Zhang, Mei; Yuan, Tiechui; Li, Ruidi; Xie, Siyao; Wang, Minbo; Weng, Qigang
Abstract: Micron-sized boron carbide (B4 C) powders were subjected to spark plasma sintering (SPS) under temperature ranging from 1700 °C to 2100 °C for a soaking time of 5, 10 and 20 min and their densification kinetics was determined using a creep deformation model. The densification mechanism was interpreted on the basis of the stress exponent n and the apparent activation energy Q d from Harrenius plots. Results showed that within the temperature range 1700–2000 °C, creep deformation which was controlled by grain-boundary sliding or by interface reaction contributed to the densification mechanism at low effective stress regime ( n = 2, Q d = 459.36 kJ/mol). While at temperature higher than 2000 °C or at high stress regime, the dominant mechanism appears to be the dislocation climb ( n = 6.11).